Cultivating a Learning Ecology in an Online Graduate Course - Trisha Barefield; Haijun Kang (Adult Education Research Conference, 2025)
This paper discusses the authors’ co-facilitation of a learning ecology in an online course on adult education program planning. Aspects and implications of an asynchronous learning ecology will be shared.
Keywords: online graduate education; learning ecology; complexity; technology